The effect of a single dose of the Thermo Speed Extreme (Olimp) thermogenic supplement on circulatory functions and body temperatures at rest in male and female subjects - ILONA POKORA; ŁUKASZ WOLOWSKI; PIOTR WYDERKA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪The purpose of the study was to examine the impact of a single dose of the Thermo Speed Extreme (TSE) supplement on circulatory functions at rest and body temperatures in men and women. Material and methods: ‪Twenty-five (male and female) subjects volunteered to participate in this study. Prior to the experiment, the anthropometric characteristics, internal and skin temperatures, the heart rate and blood pressure were measured. Then, the subjects took a single dose of the TSE or placebo (PLA) supplement in a double-blind, randomised, cross-over design. Following the supplement consumption, the same physiological parameters were registered in a seated position for 6 h. Results: ‪Statistical analysis revealed significant effects of supplement × time × sex interactions on the cardiovascular system functions. There was no significant influence of TSE on internal temperature. There was a significant effect of gender on skin temperatures and significant correlations between changes in skin temperatures and Δ SBP after TSE consumption in females. Conclusions: ‪The single dose of TSE has an effect on the circulatory and thermoregulatory systems, although the strength of this effect is sex depended. This can be expected to be due to the sex-dependent differences in skin vessels reactivity to components present in the product.